Organizational Politics in Private University, and the Performance Aspiration: Job Conflict and Stress as Mediators - Hartono, Edy (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
This study aims to determine the effect of organizational politics on the performance of the private university in Indonesia, mediated by workplace conflict and job stress. This study adheres to the quantitative explanatory approach by constructing a path analysis of PLS-SEM from the responses of 209 academic staff. The results showed that organizational politics influenced performance through mediating variables, workplace conflict and job stress. In addition to mediating organizational politics and performance, conflict and job stress affect performance in direct relationships.